THE IMPACT OF THE LEARNING AND OF THE PRACTICE OF THE SWIMMING FOR SENIORS OF THE CLUB OF THE WORKER OF SESI/AM (Fiep Bulletin - online, 2011)
This study has for objective to analyze the impact of the learning and of the practice of the swimming for the seniors of the Club of the Worker of SESI/AM. a questionnaire was applied. The treatment released to the obtained data felt through descriptive analysis (average and frequency) and content analysis. The main results appear for the possibility and the viability of a swimming program for seniors, besides this process it was fundamental for the self-esteem, the socialization and the motivation, being fundamental for the maintenance of a healthy life for the seniors.
Keywords: Learning; Senior; Swimming